2021
DOI: 10.3389/fnins.2021.620525
|View full text |Cite
|
Sign up to set email alerts
|

PPAR γ Prevents Neuropathic Pain by Down-Regulating CX3CR1 and Attenuating M1 Activation of Microglia in the Spinal Cord of Rats Using a Sciatic Chronic Constriction Injury Model

Abstract: BackgroundPrevious studies have proved that peripheral nerve injury is involved in the pathogenesis of neuropathic pain (NP). The peripheral nerve injury primes spinal M1 microglia phenotype and produces pro-inflammatory cytokines, which are responsible for neurotoxic and neuronal hyper-excitable outcomes. Spinal peroxisome proliferator-activated receptor gamma (PPAR γ) has been shown to play an anti-inflammatory role in the development of NP. However, the role of PPAR γ in attenuating the pathological pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Given the paucity of information regarding NAAA’s transcriptional control ( 10 ), a variety of scenarios appear equally plausible. One intriguing possibility is that release of colony stimulating factor 1 ( 78 ) or other cytokines (e.g., CXCL1) ( 79 ) in the dorsal horn might directly or indirectly stimulate NAAA transcription. In this regard, it is important to point out that NAAA may also be activated through a posttranslational mechanism involving the autocatalyzed cleavage of its inactive precursor ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the paucity of information regarding NAAA’s transcriptional control ( 10 ), a variety of scenarios appear equally plausible. One intriguing possibility is that release of colony stimulating factor 1 ( 78 ) or other cytokines (e.g., CXCL1) ( 79 ) in the dorsal horn might directly or indirectly stimulate NAAA transcription. In this regard, it is important to point out that NAAA may also be activated through a posttranslational mechanism involving the autocatalyzed cleavage of its inactive precursor ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, pioglitazone administration reduced elevated level of TNF-α in DRGs and spinal cord that was parallel with the alleviation of established allodynia and hyperalgesia. The centrally mediated effects of PPAR- activation have also been reported wherein several PPAR- agonists suppressed microglia and astrocytes activation, reduced the development of spinal neuroinflammation, and showed antinociceptive and neuroprotective effects [14,15,34,35]. A recent study showed decreased transcription factor in parallel with reduced expression of PPAR-γ in spinal cords after paclitaxel administration.…”
Section: Discussionmentioning
confidence: 90%
“…26,27 Recently, Li et al demonstrated that intrathecal infusion of lentivirus encoding PPAR-γ attenuated neuropathic pain. 28 Adding to this, pioglitazone readily cross blood-brain barrier and showed neuroprotection in the CNS. 14,29 Further, in order to elucidate receptor dependent effects of pioglitazone, BADGE, a PPAR-γ antagonist was employed.…”
Section: Discussionmentioning
confidence: 99%